TECHNICAL EFFICIENCY ANALYSIS IN INDONESIAN FISHERY PROCESSING INDUSTRY: A CASE OF FISHERY CANNED PRODUCT FIRMS - Munawar Asikin; Arief Daryanto; Machfud .; Subagio Dwijosumono (Universitas Mercu Buana, 2019)
This study aims to analyze technical efficiency and evaluate the effect of some sources of inefficiency in the Indonesian fishery canned firms during the period of 1990-2015. We calculate technical efficiency using the Stochastic Frontier Analysis (SFA) method with Time Varying Decay. The average of technical efficiency in this industry during the period of 1990-2015 was only 57%. It indicates that firms in this industry still encounter a problem in allocating the resources in efficient manner. However, during the period of 1994-2015, the efficiency in the Indonesian fishery canned industry has declined. We also employed the Ordinary Least Square (OLS) method to evaluate the sources of inefficiency. The results showed that eight variables affected to the efficiency in this industry, thereby it will reduce fishery product competitiveness in the future